Not all in the same boat: Trends and mechanisms in herbivory responses to forest fragmentation differ among insect guilds - Rossetti, María Rosa (2014)
Habitat fragmentation can alter fundamental ecological interactions such as insect herbivory. Few studies of habitat fragmentation effects on herbivory have examined the mechanisms involved, and differences among insect guilds have been largely ignored. Here, we studied area and edge effects on herbivory by three guilds of phytophagous insects in a fragmented Chaco Serrano forest. We estimated herbivory levels on native Croton lachnostachyus plants and assessed plant availability (distance to nearest conspeciﬁc) and quality indicators (leaf water, carbon and nitrogen content), as well as richness and abundance of the associated insect community, in order to explore mechanisms underlying herbivory changes. Herbivory by chewing and sap-sucking insects decreased, and herbivory by leaf miners increased in plants growing at the forest edge, compared with those at the interior. Forest area effects were detected only in interaction with edge effects on chewing, leaf mining and total herbivory. Lower herbivory at the edge appeared to be mediated by changes in leaf water and nitrogen content for sap-sucking herbivory, and linked to strong direct effects for chewing damage and total herbivory. Instead, higher damage levels by leaf miners at the forest edge seemed to be driven by increased plant availability and lower water content. Further studies are needed to unravel the factors involved in the strong direct effects detected here for all herbivory types. These results emphasize the necessity to consider differential responses from diverse phytophagous insect guilds, and factors operating at multiple levels, in order to disentangle, and ultimately understand, forest fragmentation effects on herbivory.